Production process of new energy automobile power battery cooling liquid with wide temperature range performance
By using the basic coolant components copolymerized by ethylene glycol and modified polyethylene glycol, and adding copolymers containing amide bonds and carboxylic acid groups as wide temperature regulators, combined with supercritical carbon dioxide extraction and molecular sieve drying and other technologies, a new energy vehicle power battery coolant with excellent wide temperature range performance was prepared, solving the problem of the degradation of traditional coolant performance at extreme temperatures, and achieving efficient heat dissipation and electrochemical stability.
Patent Information
- Application Number
- CN202411572491.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-25
AI Technical Summary
The fluidity and thermal conductivity of traditional power battery coolant in extremely high or low temperature environments have decreased, making it difficult to meet the needs of new energy vehicle power batteries under high voltage and high current conditions.
The basic coolant component composed of copolymerized by ethylene glycol and modified polyethylene glycol is used, and a copolymer containing amide bonds and carboxylic acid groups is added as a wide temperature domain regulator. Through supercritical carbon dioxide extraction, molecular sieve drying, microwave-assisted heating, ultrasonic dispersion, nanofiltration and electrodialysis, a new energy vehicle power battery coolant with excellent wide temperature domain performance was prepared.
It realizes efficient heat dissipation of power battery coolant under extreme temperature conditions, improves electrochemical stability and environmental friendliness, and meets the use needs of new energy vehicle power batteries under high voltage and high current conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery antifreeze fluid, and specifically relates to a production process of a new energy vehicle power battery coolant with wide temperature range performance. Background Art
[0002] With the transformation of the global energy structure and the improvement of environmental awareness, the new energy vehicle industry is booming at an unprecedented speed. As one of the core components of new energy vehicles, the performance of power batteries is directly related to the vehicle's range, safety and service life. Power batteries generate a lot of heat during operation. If they cannot be effectively dissipated, their working efficiency and life will be seriously affected. Therefore, as a key component of the thermal management system, the optimization of the performance of power battery coolant is crucial to improving the overall performance of new energy vehicles.
[0003] Traditional power battery coolants are mainly based on organic solvents such as ethylene glycol (EG) or propylene glycol (PG), and various additives are added to improve their thermal stability, corrosion resistance, and anti-foaming properties. However, these traditional coolants have obvious deficiencies in wide temperature range performance, especially in extremely high or low temperature environments, where their fluidity and thermal conductivity will drop significantly, thus affecting the heat dissipation effect of the power battery.
[0004] In addition, with the continuous advancement of new energy vehicle technology, the energy density and power density of power batteries are constantly increasing, and the performance requirements for coolants are becoming increasingly stringent. Traditional coolants also have certain limitations in terms of electrochemical stability and environmental friendliness, and it is difficult to meet the use requirements of new energy vehicle power batteries under high voltage and high current conditions. Summary of the invention
[0005] The purpose of the present invention is to provide a new energy vehicle power battery coolant production process with wide temperature range performance in view of the existing problems.
[0006] The present invention is achieved through the following technical solutions: A production process for a new energy vehicle power battery coolant with wide temperature range performance, characterized in that it specifically comprises the following steps: (1) Raw material selection and pretreatment: 1) Basic coolant ingredients: A new type of high boiling point and low freezing point basic coolant ingredient is selected, which is copolymerized by ethylene glycol (EG) and modified polyethylene glycol (MPEG) at a mass ratio of 70:30. The purity of ethylene glycol is not less than 99.9%, the molecular weight of modified polyethylene glycol is controlled between 1000 and 2000, and contains functional groups of amide bonds and carboxylic acid groups.
[0007] 2) Wide temperature range regulator: A copolymer containing amide bonds and carboxylic acid groups is selected as a wide temperature range regulator, and its mass accounts for 2% to 5% of the total mass of the coolant. The molecular structure of the copolymer is stable and can form a stable hydrogen bond network with water molecules, thereby improving the wide temperature range performance of the coolant.
[0008] 3) Other additives: including anti-corrosion agents (0.5% to 1% by mass), antioxidants (0.3% to 0.8% by mass), anti-foaming agents (0.1% to 0.3% by mass), etc., all of which are high-performance, low-toxic chemical reagents.
[0009] All raw materials must undergo supercritical carbon dioxide extraction and molecular sieve drying to remove trace impurities and moisture.
[0010] (2) Mixing reaction: The pretreated basic coolant components and additives are reacted at a temperature of 75°C to 85°C and a pressure of 0.25MPa to 0.35MPa for a reaction time of no more than 1 hour. Microwave-assisted heating and ultrasonic dispersion technology are used to improve the reaction efficiency and uniformity of the coolant mixture.
[0011] (3) Filtration and purification: A multi-stage filtration system combining nanofiltration technology and electrodialysis technology is used to deeply purify the coolant mixture after the reaction. The pore size of the nanofiltration membrane is controlled between 0.001 microns and 0.01 microns to remove nano-scale particles, ionic pollutants and possible microbial contamination. Electrodialysis technology is used to further remove ionic pollutants in the coolant to ensure that the clarity and purity of the coolant reach higher standards.
[0012] (4) Performance testing and adjustment: The filtered and purified coolant is tested for freezing point, boiling point, pH value, conductivity, corrosiveness, and wide temperature range performance. The freezing point should be lower than -45°C, the boiling point should be higher than 190°C, the pH value should be controlled between 7.0 and 9.0, and the conductivity should be lower than 10μs / cm. At the same time, thermal shock tests and electrochemical stability tests are added to the coolant under extreme temperature conditions to verify the stability and reliability of the coolant under rapid temperature changes and high voltage environments. Based on the test results, the coolant formula is precisely adjusted to meet the high requirements for the wide temperature range performance of new energy vehicle power batteries.
[0013] (5) Packaging and storage: Use materials with special barrier properties for packaging, such as aluminum-plastic composite film or high-density polyethylene bottles, to prevent the coolant from being corroded by air, moisture and ultraviolet rays. At the same time, set a humidity indicator card and oxygen absorber inside the package to monitor and maintain the dry environment inside the package in real time. The coolant should be stored in a cool and dry environment away from direct sunlight, and the temperature should be controlled between 5°C and 30°C.
[0014] Furthermore, in the molecular structure of the polymer compound of the wide temperature range regulator, the functional group ratio of the amide bond and the carboxylic acid group is controlled between 1:1 and 1:1.5 to form a stronger hydrogen bond network, thereby improving the wide temperature range performance of the coolant.
[0015] Furthermore, the method also includes the steps of conducting long-term cycle tests and accelerated aging tests on the coolant. The long-term cycle test simulates the long-term operating conditions of the power battery of a new energy vehicle in an actual working environment, and the accelerated aging test is conducted in a high temperature and high humidity environment to verify the stability and reliability of the coolant during long-term operation and accelerated aging.
[0016] Furthermore, the steps for preparing the copolymer of amide bonds and carboxylic acid groups specifically include: a) Raw material selection and ratio: acrylic acid (AA) is selected as the carboxylic acid group monomer, acrylamide (AM) is selected as the amide bond monomer, and the mass ratio of acrylic acid to acrylamide is 1:1 to 1:1.5, preferably 1:1.2, to ensure that the functional group ratio of the amide bond and the carboxylic acid group in the copolymer is moderate, so as to form a stronger hydrogen bond network; b) Polymerization reaction: Deionized water is selected as the reaction solvent, and its amount is 50% to 100% of the total weight of the monomers, preferably 70%, to ensure the uniformity and stability of the reaction system. Ammonium persulfate (APS) is selected as the initiator, and its amount is 0.5% to 2% of the total weight of the monomers, preferably 1%, to initiate the polymerization reaction of acrylic acid and acrylamide. Under nitrogen protection, the reaction system is heated to 70°C to 85°C, preferably 78°C, and the temperature is maintained for polymerization reaction. The reaction time is controlled between 4 hours and 8 hours, preferably 6 hours, to ensure the full progress of the polymerization reaction; c) Post-treatment: The system after the reaction is cooled to room temperature, and then an appropriate amount of ethanol is added for precipitation to remove unreacted monomers and oligomers. The precipitate is washed with deionized water several times to remove residual ethanol and impurities. Then, the washed precipitate is dried in a vacuum drying oven to constant weight to obtain a copolymer of amide bonds and carboxylic acid groups.
[0017] Furthermore, the method also includes the steps of conducting performance tests on the copolymer: conducting infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) analyses on the copolymer to confirm its chemical structure and the existence of functional groups, conducting thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analyses on the copolymer to evaluate its thermal stability and thermal transition temperature, and conducting solubility tests on the copolymer to determine its solubility and dispersibility in different solvents.
[0018] Compared with the prior art, the present invention has the following advantages: 1. It has excellent wide temperature range performance and can meet the use requirements of new energy vehicle power batteries under extreme temperature conditions.
[0019] 2. High stability and reliability, verified by long-term cycle tests and accelerated aging tests, ensure the stable performance of the coolant during long-term operation.
[0020] 3. The environmental protection characteristics are remarkable. All raw materials are strictly processed, and the additives are high-performance, low-toxic chemical reagents that meet environmental protection requirements.
[0021] 4. The preparation process is simple and efficient, easy to realize industrial production, and has broad market application prospects. DETAILED DESCRIPTION Example 1
[0022] A production process for a new energy vehicle power battery coolant with wide temperature range performance, characterized in that it specifically comprises the following steps: (1) Raw material selection and pretreatment: 1) Basic coolant ingredients: A new type of high boiling point and low freezing point basic coolant ingredient is selected, which is copolymerized by ethylene glycol (EG) and modified polyethylene glycol (MPEG) at a mass ratio of 70:30. The purity of ethylene glycol is 99.9%, the molecular weight of modified polyethylene glycol is controlled at 1000, and it contains functional groups of amide bonds and carboxylic acid groups.
[0023] 2) Wide temperature range regulator: A copolymer containing amide bonds and carboxylic acid groups is selected as a wide temperature range regulator, and its mass accounts for 2% of the total mass of the coolant. The molecular structure of the copolymer is stable and can form a stable hydrogen bond network with water molecules, thereby improving the wide temperature range performance of the coolant.
[0024] 3) Other additives: including anti-corrosion agents (0.5% by mass), antioxidants (0.3% by mass), anti-foaming agents (0.1% by mass), etc., all of which are high-performance, low-toxic chemical reagents.
[0025] All raw materials must undergo supercritical carbon dioxide extraction and molecular sieve drying to remove trace impurities and moisture.
[0026] (2) Mixing reaction: The pretreated basic coolant components and additives are reacted at a temperature of 75°C and a pressure of 0.25 MPa for 1 hour. Microwave-assisted heating and ultrasonic dispersion technology are used to improve the reaction efficiency and uniformity of the coolant mixture.
[0027] (3) Filtration and purification: A multi-stage filtration system combining nanofiltration technology and electrodialysis technology is used to deeply purify the coolant mixture after the reaction. The pore size of the nanofiltration membrane is 0.001 micron to remove nano-scale particles, ionic pollutants and possible microbial contamination. Electrodialysis technology is used to further remove ionic pollutants in the coolant to ensure that the clarity and purity of the coolant reach higher standards.
[0028] (4) Performance testing and adjustment: The filtered and purified coolant is tested for freezing point, boiling point, pH value, conductivity, corrosiveness and wide temperature range performance. The freezing point is -46°C, the boiling point is 202°C, the pH value is controlled at 8.5, and the conductivity is 7.2μs / cm. At the same time, thermal shock tests and electrochemical stability tests are added to the coolant under extreme temperature conditions to verify the stability and reliability of the coolant under rapid temperature changes and high voltage environments. Based on the test results, the coolant formula is precisely adjusted to meet the high requirements for the wide temperature range performance of new energy vehicle power batteries.
[0029] (5) Packaging and storage: Use materials with special barrier properties for packaging, such as aluminum-plastic composite film or high-density polyethylene bottles, to prevent the coolant from being corroded by air, moisture and ultraviolet rays. At the same time, set a humidity indicator card and oxygen absorber inside the package to monitor and maintain the dry environment inside the package in real time. The coolant should be stored in a cool and dry environment away from direct sunlight, and the temperature should be controlled at 25°C.
[0030] In the molecular structure of the polymer compound of the wide temperature range regulator, the functional group ratio of the amide bond and the carboxylic acid group is 1:1.2, so as to form a stronger hydrogen bond network, thereby improving the wide temperature range performance of the coolant.
[0031] The long-term cycle test simulates the long-term operating conditions of new energy vehicle power batteries in the actual working environment, and the accelerated aging test is carried out under high temperature and high humidity environment to verify the stability and reliability of the coolant during long-term operation and accelerated aging.
[0032] The steps for preparing the copolymer of amide bonds and carboxylic acid groups specifically include: a) Raw material selection and ratio: acrylic acid (AA) is selected as the carboxylic acid group monomer, acrylamide (AM) is selected as the amide bond monomer, and the mass ratio of acrylic acid to acrylamide is 1:1.2 to ensure that the functional group ratio of the amide bond and the carboxylic acid group in the copolymer is moderate to form a stronger hydrogen bond network; b) Polymerization reaction: Deionized water was selected as the reaction solvent, and its amount was 70% of the total weight of the monomers to ensure the uniformity and stability of the reaction system. Ammonium persulfate (APS) was selected as the initiator, and its amount was 1% of the total weight of the monomers to initiate the polymerization reaction of acrylic acid and acrylamide. Under nitrogen protection, the reaction system was heated to 78°C and maintained at this temperature for polymerization reaction. The reaction time was controlled within 6 hours to ensure that the polymerization reaction was fully carried out; c) Post-treatment: The system after the reaction is cooled to room temperature, and then an appropriate amount of ethanol is added for precipitation to remove unreacted monomers and oligomers. The precipitate is washed with deionized water for 3 times to remove residual ethanol and impurities. Then, the washed precipitate is dried in a vacuum drying oven to constant weight to obtain a copolymer of amide bonds and carboxylic acid groups.
[0033] The copolymers were subjected to infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) analyses to confirm their chemical structures and the presence of functional groups, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analyses to evaluate their thermal stability and thermal transition temperatures, and solubility tests to determine their solubility and dispersibility in different solvents. Example 2
[0034] A production process for a new energy vehicle power battery coolant with wide temperature range performance, characterized in that it specifically comprises the following steps: (1) Raw material selection and pretreatment: 1) Basic coolant ingredients: A new type of high boiling point and low freezing point basic coolant ingredient is selected, which is copolymerized by ethylene glycol (EG) and modified polyethylene glycol (MPEG) at a mass ratio of 70:30. The purity of ethylene glycol is 99.9%, the molecular weight of modified polyethylene glycol is 2000, and it contains functional groups of amide bonds and carboxylic acid groups.
[0035] 2) Wide temperature range regulator: A copolymer containing amide bonds and carboxylic acid groups is selected as a wide temperature range regulator, and its mass accounts for 5% of the total mass of the coolant. The molecular structure of the copolymer is stable and can form a stable hydrogen bond network with water molecules, thereby improving the wide temperature range performance of the coolant.
[0036] 3) Other additives: including anti-corrosion agents (1% by mass), antioxidants (0.8% by mass), anti-foaming agents (0.3% by mass), etc., all of which are high-performance, low-toxic chemical reagents.
[0037] All raw materials must undergo supercritical carbon dioxide extraction and molecular sieve drying to remove trace impurities and moisture.
[0038] (2) Mixing reaction: The pretreated basic coolant components and additives are reacted at a temperature of 85°C and a pressure of 0.35 MPa for a reaction time of no more than 1 hour. Microwave-assisted heating and ultrasonic dispersion technology are used to improve the reaction efficiency and uniformity of the coolant mixture.
[0039] (3) Filtration and purification: A multi-stage filtration system combining nanofiltration technology and electrodialysis technology is used to deeply purify the coolant mixture after the reaction. The pore size of the nanofiltration membrane is 0.01 micron to remove nano-scale particles, ionic pollutants and possible microbial contamination. Electrodialysis technology is used to further remove ionic pollutants in the coolant to ensure that the clarity and purity of the coolant reach higher standards.
[0040] (4) Performance testing and adjustment: The filtered and purified coolant is tested for freezing point, boiling point, pH value, conductivity, corrosiveness and wide temperature range performance. The freezing point is -48°C, the boiling point is 198°C, the pH value is controlled at 8.1, and the conductivity is 6.5μs / cm. At the same time, thermal shock tests and electrochemical stability tests are added to the coolant under extreme temperature conditions to verify the stability and reliability of the coolant under rapid temperature changes and high voltage environments. Based on the test results, the coolant formula is precisely adjusted to meet the high requirements for the wide temperature range performance of new energy vehicle power batteries.
[0041] (5) Packaging and storage: Use materials with special barrier properties for packaging, such as aluminum-plastic composite film or high-density polyethylene bottles, to prevent the coolant from being corroded by air, moisture and ultraviolet rays. At the same time, set a humidity indicator card and oxygen absorber inside the package to monitor and maintain the dry environment inside the package in real time. The coolant should be stored in a cool and dry environment away from direct sunlight at a temperature of 30°C.
[0042] In the molecular structure of the polymer compound of the wide temperature range regulator, the functional group ratio of the amide bond and the carboxylic acid group is controlled at 1:1.5 to form a stronger hydrogen bond network, thereby improving the wide temperature range performance of the coolant.
[0043] The long-term cycle test simulates the long-term operating conditions of new energy vehicle power batteries in the actual working environment, and the accelerated aging test is carried out under high temperature and high humidity environment to verify the stability and reliability of the coolant during long-term operation and accelerated aging.
[0044] The steps for preparing the copolymer of amide bonds and carboxylic acid groups specifically include: a) Raw material selection and ratio: acrylic acid (AA) is selected as the carboxylic acid group monomer, acrylamide (AM) is selected as the amide bond monomer, and the mass ratio of acrylic acid to acrylamide is 1:1 to ensure that the functional group ratio of the amide bond and the carboxylic acid group in the copolymer is moderate to form a stronger hydrogen bond network; b) Polymerization reaction: Deionized water was selected as the reaction solvent, and its amount was 50% of the total weight of the monomers to ensure the uniformity and stability of the reaction system. Ammonium persulfate (APS) was selected as the initiator, and its amount was 0.5% of the total weight of the monomers to initiate the polymerization reaction of acrylic acid and acrylamide. Under nitrogen protection, the reaction system was heated to 70°C and maintained at this temperature for polymerization reaction. The reaction time was controlled within 4 hours to ensure that the polymerization reaction was fully carried out; c) Post-treatment: The system after the reaction is cooled to room temperature, and then an appropriate amount of ethanol is added for precipitation to remove unreacted monomers and oligomers. The precipitate is washed with deionized water for 3 times to remove residual ethanol and impurities. Then, the washed precipitate is dried in a vacuum drying oven to constant weight to obtain a copolymer of amide bonds and carboxylic acid groups.
[0045] The copolymers were subjected to infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) analyses to confirm their chemical structures and the presence of functional groups, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analyses to evaluate their thermal stability and thermal transition temperatures, and solubility tests to determine their solubility and dispersibility in different solvents. Example 3
[0046] A production process for a new energy vehicle power battery coolant with wide temperature range performance, characterized in that it specifically comprises the following steps: (1) Raw material selection and pretreatment: 1) Basic coolant ingredients: A new type of high boiling point and low freezing point basic coolant ingredient is selected, which is copolymerized by ethylene glycol (EG) and modified polyethylene glycol (MPEG) at a mass ratio of 70:30. The purity of ethylene glycol is 99.9%, the molecular weight of modified polyethylene glycol is controlled at 2000, and it contains functional groups of amide bonds and carboxylic acid groups.
[0047] 2) Wide temperature range regulator: A copolymer containing amide bonds and carboxylic acid groups is selected as a wide temperature range regulator, and its mass accounts for 5% of the total mass of the coolant. The molecular structure of the copolymer is stable and can form a stable hydrogen bond network with water molecules, thereby improving the wide temperature range performance of the coolant.
[0048] 3) Other additives: including anti-corrosion agents (1% by mass), antioxidants (0.8% by mass), anti-foaming agents (0.1% by mass), etc., all of which are high-performance, low-toxic chemical reagents.
[0049] All raw materials must undergo supercritical carbon dioxide extraction and molecular sieve drying to remove trace impurities and moisture.
[0050] (2) Mixing reaction: The pretreated basic coolant components and additives are reacted at a temperature of 85°C and a pressure of 0.25 MPa for 1 hour. Microwave-assisted heating and ultrasonic dispersion technology are used to improve the reaction efficiency and uniformity of the coolant mixture.
[0051] (3) Filtration and purification: A multi-stage filtration system combining nanofiltration technology and electrodialysis technology is used to deeply purify the coolant mixture after the reaction. The pore size of the nanofiltration membrane is controlled at 0.005 microns to remove nano-scale particles, ionic pollutants and possible microbial contamination. Electrodialysis technology is used to further remove ionic pollutants in the coolant to ensure that the clarity and purity of the coolant reach higher standards.
[0052] (4) Performance testing and adjustment: The filtered and purified coolant is tested for freezing point, boiling point, pH value, conductivity, corrosiveness and wide temperature range performance. The freezing point is -50°C, the boiling point is 210°C, the pH value is controlled at 7.9, and the conductivity is 6.7μs / cm. At the same time, thermal shock tests and electrochemical stability tests are added to the coolant under extreme temperature conditions to verify the stability and reliability of the coolant under rapid temperature changes and high voltage environments. Based on the test results, the coolant formula is precisely adjusted to meet the high requirements for the wide temperature range performance of new energy vehicle power batteries.
[0053] (5) Packaging and storage: Use materials with special barrier properties for packaging, such as aluminum-plastic composite film or high-density polyethylene bottles, to prevent the coolant from being corroded by air, moisture and ultraviolet rays. At the same time, set a humidity indicator card and oxygen absorber inside the package to monitor and maintain the dry environment inside the package in real time. The coolant should be stored in a cool and dry environment away from direct sunlight, and the temperature should be controlled at 25°C.
[0054] In the molecular structure of the polymer compound of the wide temperature range regulator, the functional group ratio of the amide bond and the carboxylic acid group is controlled at 1:1.5 to form a stronger hydrogen bond network, thereby improving the wide temperature range performance of the coolant.
[0055] The long-term cycle test simulates the long-term operating conditions of new energy vehicle power batteries in the actual working environment, and the accelerated aging test is carried out under high temperature and high humidity environment to verify the stability and reliability of the coolant during long-term operation and accelerated aging.
[0056] The steps for preparing the copolymer of amide bonds and carboxylic acid groups specifically include: a) Raw material selection and ratio: acrylic acid (AA) is selected as the carboxylic acid group monomer, acrylamide (AM) is selected as the amide bond monomer, and the mass ratio of acrylic acid to acrylamide is 1:1.5 to ensure that the functional group ratio of the amide bond and the carboxylic acid group in the copolymer is moderate to form a stronger hydrogen bond network; b) Polymerization reaction: Deionized water is selected as the reaction solvent, and its amount is 80% of the total weight of the monomers to ensure the uniformity and stability of the reaction system. Ammonium persulfate (APS) is selected as the initiator, and its amount is 2% of the total weight of the monomers to initiate the polymerization reaction of acrylic acid and acrylamide. Under nitrogen protection, the reaction system is heated to 85°C and maintained at this temperature for polymerization reaction. The reaction time is controlled within 8 hours to ensure that the polymerization reaction is fully carried out; c) Post-treatment: The system after the reaction is cooled to room temperature, and then an appropriate amount of ethanol is added for precipitation to remove unreacted monomers and oligomers. The precipitate is washed twice with deionized water to remove residual ethanol and impurities. Then, the washed precipitate is dried in a vacuum drying oven to constant weight to obtain a copolymer of amide bonds and carboxylic acid groups.
[0057] The copolymers were subjected to infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) analyses to confirm their chemical structures and the presence of functional groups, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analyses to evaluate their thermal stability and thermal transition temperatures, and solubility tests to determine their solubility and dispersibility in different solvents.
[0058] The performance indicators of the new energy vehicle power battery coolant production process embodiments 1-3 with wide temperature range performance are as follows:
[0059] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. A production process for a new energy vehicle power battery coolant with wide temperature range performance, characterized in that: The specific steps include: (1) Raw material selection and pretreatment: All raw materials must be extracted with supercritical carbon dioxide and dried with molecular sieves. The raw materials include: 1) Basic coolant ingredients: A new type of high boiling point and low freezing point basic coolant ingredient is selected, which is copolymerized by ethylene glycol (EG) and modified polyethylene glycol (MPEG) at a mass ratio of 70:
30. The purity of ethylene glycol is not less than 99.9%, and the molecular weight of modified polyethylene glycol is controlled between 1000 and 2000, and contains functional groups of amide bonds and carboxylic acid groups; 2) Wide temperature range regulator: A copolymer containing an amide bond and a carboxylic acid group is selected as a wide temperature range regulator, and its mass accounts for 2% to 5% of the total mass of the coolant; 3) Other additives: including anti-corrosion agents (0.5% to 1% by mass), antioxidants (0.3% to 0.8% by mass), and anti-foaming agents (0.1% to 0.3% by mass); (2) Mixing reaction: reacting the pretreated basic coolant components and additives at a temperature of 75°C to 85°C and a pressure of 0.25MPa to 0.35MPa for a reaction time of no more than 1 hour, and using microwave-assisted heating and ultrasonic dispersion technology; (3) Filtration and purification: A multi-stage filtration system combining nanofiltration technology and electrodialysis technology is used to deeply purify the coolant mixture after the reaction. The pore size of the nanofiltration membrane is controlled between 0.001 microns and 0.01 microns; (4) Performance testing and adjustment: The filtered and purified coolant is tested for freezing point, boiling point, pH value, conductivity, corrosiveness, and wide temperature range performance. The freezing point should be lower than -45°C, the boiling point should be higher than 190°C, the pH value should be controlled between 7.0 and 9.0, and the conductivity should be lower than 10μs / cm. At the same time, thermal shock tests and electrochemical stability tests are added to the coolant under extreme temperature conditions. Based on the test results, the coolant formula is adjusted accurately. (5) Packaging and storage: Use materials with special barrier properties for packaging, such as aluminum-plastic composite film or high-density polyethylene bottles; at the same time, set a humidity indicator card and oxygen absorber inside the package; the coolant should be stored in a cool and dry environment away from direct sunlight, and the temperature should be controlled between 5°C and 30°C.
2. The production process of a new energy vehicle power battery coolant with wide temperature range performance according to claim 1, characterized in that: In the molecular structure of the polymer compound of the wide temperature range regulator, the functional group ratio of the amide bond and the carboxylic acid group is controlled between 1:1 and 1:1.
5.
3. The manufacturing method according to claim 1, characterized in that: It also includes steps for long-term cycle testing and accelerated aging testing of the coolant. The long-term cycle test simulates the long-term operating conditions of new energy vehicle power batteries in the actual working environment, while the accelerated aging test is carried out under high temperature and high humidity conditions.
4. The production process of a new energy vehicle power battery coolant with wide temperature range performance according to claim 1, characterized in that: The method also includes the steps of preparing a copolymer of amide bonds and carboxylic acid groups, specifically comprising: a) Raw material selection and ratio: acrylic acid (AA) is selected as the carboxylic acid group monomer, acrylamide (AM) is selected as the amide bond monomer, and the mass ratio of acrylic acid to acrylamide is 1:1 to 1:1.5, preferably 1:1.2; b) Polymerization reaction: Deionized water is selected as the reaction solvent, and its amount is 50% to 100% of the total mass of the monomer, preferably 70%. Ammonium persulfate (APS) is selected as the initiator, and its amount is 0.5% to 2% of the total mass of the monomer, preferably 1%. Under nitrogen protection, the reaction system is heated to 70°C to 85°C, preferably 78°C, and the temperature is maintained for polymerization reaction. The reaction time is controlled between 4 hours and 8 hours, preferably 6 hours; c) Post-treatment: The system after the reaction is cooled to room temperature, and then ethanol is added for precipitation, and the precipitate is washed with deionized water for 2-3 times, and then the washed precipitate is dried in a vacuum drying oven to constant weight to obtain a copolymer of amide bonds and carboxylic acid groups.
5. The production process of a new energy vehicle power battery coolant with wide temperature range performance according to claim 4, characterized in that: The method also includes the steps of performing performance tests on the copolymer: performing infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) analyses on the copolymer to confirm its chemical structure and the presence of functional groups, performing thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) on the copolymer to evaluate its thermal stability and thermal transition temperature, and performing solubility tests on the copolymer to determine its solubility and dispersibility in different solvents.
Citation Information
Cited By
Wide-temperature-range rapid-infiltration rapid-hardening self-repairing thin-layer concrete repairing material and preparation method thereof
CN121913754A
Wide-temperature-range fast-bleeding quick-setting self-repairing thin-layer concrete repair material and preparation method thereof
CN121913754B